Exploring English Medium Instruction in Nepal: A Survey of Teacher Perspectives - Maharjan, Laxmi Bahadur (Mangal Research Journal, 2025)
This study investigates the implementation of English Medium Instruction (EMI) in Nepal from the perspectives of teachers who are directly involved in classroom practice. As EMI is expanding across Nepalese schools, it has become important to understand how teachers perceive its demands, their level of preparedness, and the challenges they experience in multilingual classroom contexts. The study employed a descriptive survey design and used a structured online questionnaire to collect data from 52 EMI teachers from different provinces of Nepal. The participants were selected through convenience sampling. Data were collected over a period of three weeks using Google Forms. Informed consent was obtained from all participants, and anonymity was ensured. The study explored teachers’ perceptions across six thematic areas: demographic and professional profile of EMI teachers; EMI training and preparedness; classroom practices and challenges; EMI policy, support, and institutional practice; EMI impact on learners and stakeholders’ perceptions; and cultural sensitivity and multilingual inclusion. Descriptive statistics such as frequency, percentage, and mean were used to analyze the responses, and the findings were organized thematically. The findings indicate that although teachers generally support EMI, many report limited training and inadequate institutional support. This situation directly affects classroom delivery and student understanding. The study recommends the development of targeted EMI training programs, improved resource allocation, and clearer policy support to strengthen the quality and sustainability of EMI in Nepalese schools.